The Relationship Between Physical Activity and Student Depression Throughout Online Learning During The Covid-19 Pandemic - Berliana Yogiyanti; Tri Laksono; Dika Rizki Imania (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
WHO declared the start of the Covid-19 pandemic on March 12, 2020. To combat Covid-19, the Indonesian government implemented a Large-Scale Social Restriction (PSBB) policy that prohibited the public from engaging in outdoor activities. As a result of limitations in doing outside activities, limitations in socializing, and increasing work demands, there is a decrease in physical activity as more daily activities are spent at home. As a result, the emotional state of physiotherapy students at the University of Aisyiyah Yogyakarta becomes unstable, resulting in depression. Many people who experience depression do not have the motivation to do other activities or activities because of the onset of depression. This study aims to determine the relationship between physical activity and student depression throughout online learning during the Covid-19 pandemic. This research employed observational analytic with a cross sectional design. The research sample was taken by purposive sampling technique with a total sample of 154 respondents. The research instrument used the International Physical Activity Questionnaire (IPAQ) and the Depression Anxiety Stress Scales (DASS 21) questionnaire. The data was analyszed using univariate analysis and bivariate analysis, specifically the Spearman Rank correlation test. The results of the Spearman Rank correlation test showed that there was a significant relationship between physical activity and depression (r = -0.340, p = 0.000). There was also a significant relationship between physical activity and anxiety (r = -0.269, p = 0.001). There was also a significant relationship between physical activity and stress (r = -0.271, p = 0.001).